Thyroglobulin levels in COVID-19-positive patients: Correlations with thyroid function tests, inflammatory markers, and glucocorticoid use - Świątkowska-Stodulska, Renata; Berlińska, Agata; Puchalska-Reglińska, Ewelina (Frontiers in Endocrinology, 2023)
COVID-19 often results in generalized inflammation and affects various organs and systems. Endocrine research focused on the possible sequelae of COVID-19, with special interest given to the thyroid gland. Clinical problems such as thyroid function in non-thyroidal illness (NTI), autoimmune thyroiditis, and COVID-19-related subacute thyroiditis (SAT) quickly gained wide coverage. Thyrotoxicosis of various origins leads to the release of peripheral thyroid hormones and thyroglobulin (TG), the main glycoprotein contained within the thyroid follicular lumen. In our study, we evaluated TG levels in COVID-19-positive patients and investigated the possible relationships between TG, thyroid function tests, and inflammatory markers. Our approach included separate subanalyses of patients who received and those who did not receive glucocorticoids (GCs). In the entire population studied, the concentration of TG tended to decrease with time (p<0.001; p1,2=0.025, p1,3=0.001, p2,3=0.003), and this pattern was especially clear among patients treated with GCs (p<0.001; p1,2=<0.001; p1,3=<0.001; p 2,3=<0.001). The concentration of TG differed significantly between patients treated and those not treated with GC at the second and third time points of observation (p=0.033 and p=0.001, consecutively). TG concentration did not differ between the patients with normal and abnormal thyroid function tests (TFTs). The correlations between TG, TFTs, and inflammatory markers were very limited. 19 patients had elevated TG levels, but only one of them showed a complete TFT pattern typical of thyrotoxicosis. There were no statistically significant differences between patients who met and those who did not meet the predefined combined primary endpoint.